INTEGRASI PENILAIAN PORTOFOLIO DALAM PEMBELAJARAN PAI DI MADRASAH - Syamsuddin, - -; Asy’ariy, - - (Al Tadib : Jurnal Ilmu Pendidikan, 2016)
This article is aimed at discussing the integration of portfolio assessment in learning PAI in Madrasah. Integration of portfolio assessment in learning PAI has major advantages, namely the involvement of learners actively and creatively in the overall process of learning and assessment. With measurable planning, learning is not out of context, and oriented towards sustainable progress, students are positioned as subjects rather than objects of learning and teaching. Portfolio not only as a way of assessment but could serve as a learning strategy. With a portfolio of all aspects of the domain capable of optimally explored through the involvement of students in the whole process of learning and assessment Keywords: Portfolio assessment, Learning